2019
DOI: 10.31674/mjn.2019.v10i04.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Jaw Relaxation Technique on Low Back Pain and Selected Vital Signs Among Nursing Staff: A Randomized Controlled Trial

Abstract: Low back pain has been documented as the major common reason of absenteeism among nursing staff (d'Errico et al., 2013). Nurses ranked the sixth highest with regard to nonattendance in the working days related to musculoskeletal disorders (Dhyani, Siddhartha & Sen, 2015). They are the main hospital staff who always

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Previous studies have also reported a reduction in low back pain after administering treatments targeting the temporomandibular joint. 18,19 In the present study, both groups showed significant improvements in pain, disability, and abdominal muscle endurance at weeks six and 12 (P<0.001). This is in agreement with Chan et al 20 study showed that a six-week duration of lumbar stability exercise is an effective intervention in chronic non-specific low back pain.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have also reported a reduction in low back pain after administering treatments targeting the temporomandibular joint. 18,19 In the present study, both groups showed significant improvements in pain, disability, and abdominal muscle endurance at weeks six and 12 (P<0.001). This is in agreement with Chan et al 20 study showed that a six-week duration of lumbar stability exercise is an effective intervention in chronic non-specific low back pain.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies have also reported a reduction in low back pain after administering treatments targeting the temporomandibular joint. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%